In vitro safety & quality analysis on three species of Tongkat Ali plants & their in vivo elevation of testosterone in fowls - Sharifah Aminah, Tuan Said; Jaya Vejayan, Palliah; Yasmin Amirah, Che Yahya (Penerbit Universiti Malaysia Pahang, 2023)
Eurycoma longifolia, Polyathia bullata, and Stema tuberosa are three species of plants sharing the synonym of "Tongkat Ali" and commonly known as Tongkat Ali Putih, Tongkat Ali Hitam, and Tongkat Ali Merah, respectively. However, less study has been done on its effectiveness to increase testosterone by P. bullata and S. tuberosa compared to E. longifolia. In this study, all three types of Tongkat Ali were compared for their testosterone elevations in fowls. The roots of the plants were encapsulated and given to fowls. Before being tested on animals, the capsules' content was analyzed on a few safety and quality parameters, i.e., pH and moisture tests, heavy metal content, microbial load, and steroid presence. A total of 12 mg of each Tongkat Ali powdered material included in a capsule and given to 14 fowls for 30 days. The outcome showed an increase in testosterone in fowls with the highest value of 9.73 ± 1.20 nmol/L obtained by P. bullata, followed by E. longifolia and S. tuberosa, 7.70 ± 0.59 nmol/L, and 6.25 ± 0.70 nmol/L, respectively compared to the control of only 4.08 ± 0.85 nmol/L. The results showed that P. bullata and S. tuberosa were safe to consume (in vitro) and able to increase testosterone level in the fowls (in vivo). Thus, it also provide added information on the less studied Tongkat Ali plants and their potential as an aphrodisiac plants.